The Decline of the US Labor Share Across Sectors. (4th November 2020) - Mendieta‐Muñoz, Ivan; Rada, Codrina; von Arnim, Rudi
Abstract : We provide novel insights on the functional distribution of income in the postwar US economy, based on a Log Mean Divisia Index decomposition of the labor share by 14 sectors. We identify contributions from four components: real compensation, labor productivity, employment shares, and relative prices. The results are presented for the entire period as well as golden age (1948–1979) and neoliberal era (1979–2017), painting a detailed picture of structural changes. We find that (1) real compensation and labor productivity dominate; (2) manufacturing plays an important role in the recent decline of the labor share; (3) employment shifts toward service sectors with higher labor shares have buffered the decline; and (4) relative prices of services are increasing. We discuss these results in the context of Baumol's and Lewis's seminal contributions. Both theories build on the notion of coexistence of progressive and stagnant activities, which is documented in our sectoral decomposition.